Photoshop CS2 for digital photographers only - Milburn, Ken (Wiley, 2006)
When digital technology costs you time, it costs you money. The secret is a streamlined, logical workflow, and that's what fellow digital photographers Ken Milburn and Doug Sahlin are about to give you. By editing images without destroying the original, storing them for easy access, taking advantage of Camera Raw and the Adobe Bridge, and using the hundreds of other tips in this book, you'll be able to spend less time before the monitor and more behind the lens.